Analysis of the current state of computer systems in the field of virtual healthcare - Khrulov, Mykola (Technologies and Engineering, 2025)
The purpose of this study was to develop a conceptual model for the integration of modern digital technologies in the healthcare sector with adaptation to Ukrainian conditions and the creation of a single national medical ecosystem. The study was based on a systematic analysis of literature sources using content analysis and a systematic approach. Publications, review papers, and official documents available in leading scientific databases (PubMed, Scopus, and Web of Science) over the past five years were used to collect data. The research algorithm included preliminary selection of sources according to the criteria of relevance, reliability, and scientific significance, further analysis of technological solutions in the areas of telemedicine, artificial intelligence and virtual reality, and assessment of their integration compatibility with existing electronic health systems. The analysis covered the economic, ethical, and legal aspects of implementing innovative technologies. The results showed that telemedicine contributes to improving access to health services in remote regions, but its implementation is limited due to imperfect infrastructure and the lack of uniform regulatory standards. Analysis of artificial intelligence algorithms has shown their high potential in diagnosing and predicting diseases, which indicates the need to adapt technologies to local conditions. Research on the possibilities of virtual reality has confirmed its effectiveness in therapy, rehabilitation, and medical education, although implementation is accompanied by technical difficulties. The developed conceptual model considers both technical and organisational factors of digitalisation of healthcare, which can become the basis for strategic planning of further experimental implementations in the national health system. Thus, the analysis identified the main trends and problem areas of digital technology implementation that contribute to improving the quality of medical services and optimising resources. The results of the study form the scientific basis for developing practical measures and strategies for digitalisation adapted to the conditions of Ukrainetelemedicine; virtual reality